IDENTIFICATION OF A PERSON BY THE DNA OF THE PULP OF THE TOOTH - S. V. Syrak; I. A. Gatilo; Yu. S. Mazevskaya (Кубанский научный медицинский вестник, 2018)
Aim. The study was designed for conducting a molecular genetic analysis of DNA of the tooth pulp and establishing the genetic relationship of the child and the parent.Materials and methods. The tooth number 16 of the claimed father was provided for the DNA extraction. Saliva samples and DNA preparations of the prospective daughter were obtained for the study. In the course of the research, the M-sorbbone reagent kit was used to isolate DNA from the bone powder.Results. The conducted studies have shown that the DNA preparations isolated from a tooth and the N sample of saliva have the following genotypic allelic combinations. It was established that for each of the studied STP systems in the genome of the claimed father an allele is found, which formally coincides with the allele of conditionally paternal (nonmaternal) origin in the child’s genome.Conclusion. As shown by the results of the study, the only carrier of DNA in a forensic medical molecular genetic examination, in this case, was a tooth, namely, pulp, which was protected by the durable tissues – dentin and enamel. The uniqueness of this case lies in the fact that it is the pulp that is the only tissue that retains the genetic information making it possible to state the high probability of the claimed relationship of the father and the child.